Endophytes of forest trees biology and applications - Pirttila, Anna Maria; Frank, A. Carolin (Forestry sciences, 2011)
Found in every plant species, the diversity of endophytic micro-organisms can be extremely high within different plant organs and tissue types. In trees, their ecological roles with respect to host tree can vary from latent pathogens or saprophytes to neutral commensalists and mutualists. Given their high diversity, and their bio-active nature, endophytes are currently being associated with a role in tree health against insect herbivores and fungal pathogens, as well as improving tree properties in phytoremediation. Meanwhile there is increasing interest in the potential of some tree endophyte.